Doomscrolling dan Kecemasan Eksistensial Generasi Z: Model Konseling Kognitif-Perilaku dalam Konteks Budaya Indonesia - Nailul Mukorobin; Zamroni Zamroni; Abdurrohim Abdurrohim (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Doomscrolling, the compulsive tendency to consume negative content on social media, has become an increasingly disturbing phenomenon among Generation Z in Indonesia and has the potential to trigger existential anxiety deep anxiety regarding the meaning of life, death, and self-alienation. This study aims to examine the relationship between doomscrolling, fear of missing out (FoMO), and existential anxiety, and to formulate a cognitive-behavioral counseling model contextualized to the collectivistic culture and Islamic religiosity in Indonesia. The study used a quantitative correlational approach involving 230 Generation Z respondents who are active social media users, selected through a purposive sampling technique. Data were collected using three validated instruments, namely the Social Media Doomscrolling Scale, the Existential Anxiety Questionnaire, and the Fear of Missing Out Scale, then analyzed using correlation tests and multiple regressions in SPSS. Theoretical studies show that doomscrolling is related to existential anxiety through the mechanisms of erosion of basic assumptions about the world (Shattered Assumption Theory) and activation of death anxiety (Terror Management Theory), which is reinforced by the unmet need for social connectedness (FoMO). This study confirms that the cognitive-behavioral counseling model for Indonesian Generation Z needs to integrate cognitive restructuring with spiritual-religious values such as dhikrullah, sabr, and tawakkal, so that the intervention is more relevant and culturally acceptable. These findings are expected to provide theoretical and practical contributions to the development of Guidance and Counseling services in the digital era.